Using patient-reported outcome measures to assess the effectiveness of social media networking programs for people living with overweight and obesity to adopt a healthier lifestyle - Saadi, Alend; Fellrath, Jean-Marc; Bec-Moussally, Joanna; Papastathi-Boureau, Chrysoula; Blanc, Céline; Courtine, Valentin; Vanini, Léo; Marechal, Marc; Authier, Florence; Curty, Bertrand; Fournier, Pierre; Diana, Michele; et al. (Frontiers in Public Health, 2023)
Introduction: Overweight, obesity, and their associated health complications have become a major public health issue. Online approaches are rarely tried to address the problem. The aim of this study was to evaluate the effectiveness of using social media networking to adopt a healthier lifestyle for people living with overweight and obesity with a three-month multidisciplinary health program. The efficiency was assessed questionnaires on patient-related outcome measures (PROMs). Methods: Two non-profit associations designed the program delivered in a closed group via Facebook, the popular social network, for people living with overweight and obesity. The three-month program had three main axes, namely nutrition, psychology, and physical activity. Anthropomorphic data and socio-demographic profiles were collected. Quality of life (QOL) was assessed at the beginning and at the end of the intervention using PROM questionnaires for six different domains, i.e., body image, eating behavior, physical, sexual, social, and psychological functioning. Results: Six hundred and twenty persons participated in the program; 567 persons consented for the study, and 145 entirely completed the questionnaires. QOL was significantly improved in 5 out of 6 domains, i.e., body image, eating behavior, as well as physical, sexual, and psychological functioning. The improvement was valid regardless of age, gender, initial body mass index, person with or without children, educational level (primary versus secondary versus high school), and occupation (employment compared to unemployment or any kind of social assistance). In multivariate analysis, living as a couple was an independent factor correlated to a positive progression in four domains, i.e., body image, eating behavior, as well as physical and psychological functioning. Conclusion: This study showed that an online lifestyle intervention may be a promising way of improving the quality of life of people living with overweight or obesity.